(3GdJNWjW GdEbJUGOj ef efXhQ ESdGej (B/s - (3dWaj, HTQ eMeO ehabs ((3YeGf(B: s (3OGQ GdfaGFS ddfTQ hGdJhRjY(B, s, 2012)
(3GdJNWjW GdEbJUGOj eagheg heTQhYjJg(B- (3CgOGa GdJNWjW GdEbJUGOj GdESdGej heLGdGJg(B- (3VhGHW GdJNWjW GdEbJUGOj GdESdGej hHYV GdCSGSjGJ ajgs
(3GdeQGLY U(B.247s
Keywords: (3GdEbJUGOs; (3GdEbJUGO GdESdGejs; (3GdJNWjW GdEbJUGOjs